2013
DOI: 10.1186/1756-9966-32-16
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of VEGFR-2, PDGFR-β, and c-Met in advanced hepatocellular carcinoma

Abstract: BackgroundWe explore the clinical and prognostic significance of expression of vascular endothelial growth factor receptor (VEGFR)-2, platelet-derived growth factor receptor (PDGFR)-β, and c-Met in patients with hepatocellular carcinoma (HCC).MethodsThe expression of VEGFR-2, PDGFR-β, and c-Met were determined by immunohistochemical examination of the tissues of 93 HCC patients. The relationships of these markers with clinicopathological factors and prognosis were then analyzed.ResultsHigh expression of VEGFR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 21 publications
5
60
1
1
Order By: Relevance
“…The HGF-MET cascade is associated with hepatocarcinogenesis (19). Elevated HGF levels have been associated with poor prognosis in patients with hepatocellular carcinoma (15), and high expression of c-MET has been associated with poor outcomes in patients with hepatocellular carcinoma treated with sorafenib (20). The current clinical results, showing that elevated HGF levels at baseline were associated with significantly shorter OS in patients with advanced hepatocellular carcinoma, are consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 81%
“…The HGF-MET cascade is associated with hepatocarcinogenesis (19). Elevated HGF levels have been associated with poor prognosis in patients with hepatocellular carcinoma (15), and high expression of c-MET has been associated with poor outcomes in patients with hepatocellular carcinoma treated with sorafenib (20). The current clinical results, showing that elevated HGF levels at baseline were associated with significantly shorter OS in patients with advanced hepatocellular carcinoma, are consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies have reported on the association between alterations in MET and poor prognosis and/or disease severity in human cancers (25)(26)(27)(28). These findings support the hypothesis that specific alterations in MET may provide predictive capacity for identifying patients most likely to benefit from MET inhibitor therapy.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, the HGF/MET signaling pathway has been shown to be activated during the genesis and progression of hepatocellular carcinoma. Many reports have highlighted the prevalence of MET gene and protein expression in hepatocellular carcinoma, and have investigated the role of MET signaling in hepatocellular carcinoma progression and maintenance (24)(25)(26)(27)(28). The importance of MET signaling in these processes suggests that the status of MET gene amplification and/or protein expression in patients with hepatocellular carcinoma may serve as potential biomarkers for prognosis or response to anti-HGF/MET therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatocyte growth factor (HGF)-MET axis has been implicated as a key player in hepatocarcinogenesis based on preclinical work and as such is another logical target for HCC drug development [61][62][63][64][65][66][67]. MET overexpression occurs in 20 to 81 % of human HCC tumors, with variation based on the method of assessment [68][69][70][71][72][73]. High-level MET expression has been linked with more aggressive clinicopathologic parameters in several studies.…”
Section: Second-line Systemic Therapy-anti-angiogenesis and Beyondmentioning
confidence: 99%